(untitled) (Tikrit Journal of Pharmaceutical Sciences, 2023)
Aim of the study: to determine the effect of Rheumatoid Arthritis(RA) on liver enzymes level. Methods: 75 subjects were enrolled in this study (40 patients with Rheumatoid arthritis (RA) and 35 healthy subjects as control group), at Mosul city, Northern of Iraq, aged 20-70 years. The biochemical parameters measured were some of liver function tests which include measurement of the liver enzymes activity of aspartate aminotransferase (AST), alanine aminotransferase (ALT), alkaline phosphatase (ALP) and gamma glutamyl transferase (GGT). Results: There was a significant increase in liver enzymes activity in patients when compared to control. There was also significant increase in serum AST level at age group 40-50 years when compared to other age group in patients, in addition, there was a significant increase in serum ALP in female patients when compared to male patients. There was non-significant change in liver enzymes activity when compared according to residence, according to family history, and according to rheumatoid factor in patients. Conclusion: The results of the present study indicated no deterioration in liver functions in patients with rheumatoid arthritis regarding serum enzymes (aspartate transaminase, alanin transaminase, gamma glutamyl transferase and alkaline phosphatase), although subclinical alteration in liver functions could be expected in those patients, so that measurement of other early markers of liver dysfunction is occasionally recommended.